EKSPLORASI JENIS AMFIBI DI SEPANJANG PINGGIRAN DANAU SIPIN JAMBI, SUMATERA TENGAH - Ade Adriadi; Asrizal Paiman; Rini Indriani (Bioma, 2023)
This study aimed to determine the diversity of amphibian species in different habitat types along shore of Lake Sipin. This study used a combination of path (Transect) and VES (Visual Encounter Survey) methods. Research area was determined using purposive sampling based on the function of the habitat and the number of prey animals. The population in this study was all amphibians in the Sipin Lake. The samples were all amphibians caught using fishing nets or bare hands. Identification of amphibian species found in the lake used field guidebooks and online-based guide. The results of research carried out along the edge of Lake Sipin showed 215 individuals, 8 species and 4 families were found to be amphibians. The diversity index for amphibian species generally shows an H' index with an H' value of 1.19, which is included in the medium diversity index value. The overall amphibian species evenness index value is classified as an unstable community (E=0.573) and the amphibian species richness index value generally shows a low species richness index (Dmg=1.303). Meanwhile, the value of the community similarity index or Index of Similarity (IS) generally shows that natural habitats and tourism are relatively high with an index value of 90%.